Live Coding: A User's Manual - Blackwell, Kenneth; Cocker, Emma; Cox, Geoffrey -1951; McLean, Alex 1975-; Magnusson, Thor (Cambridge, Massachusetts The MIT Press, 2022)
"A multi-authored comprehensive introduction to live coding's potential open up deeper questions about contemporary cultural production and computational culture"--
Includes bibliographical references (pages [295]-320) and index.
Keywords: Computer science; Philosophy; Performance